ACCESS TO COGNITIVE RESOURCES IN EARLY LIFE AND TRANSITIONS ACROSS COGNITIVE STATES IN MIDDLE AND OLDER ADULTHOOD. (16th November 2018) - Lewis, N; Yoneda, T; Knight, J; DeVito, A; Muniz Terrera, G
Abstract: An expanding body of research highlights that a cognitively engaged lifestyle may protect against neurodegeneration in late life (e.g., thereby promoting cognitive reserve). The majority of research in this area uses education as a proxy to investigate the cognitive reserve hypothesis; however, more recent findings suggest that other factors from the lifespan contribute to cognitive reserve. The current study examined whether access to cognitive resources in childhood (e.g., number of books at home) influenced healthy and impaired life expectancies using coordinated analyses of data from eight countries. Multistate survival models examined transitions between healthy, mild, and severely impaired cognitive states and death, which were used to compute life expectancies for individuals with and without impairment. Controlling for age, sex, education, SES, and country, analyses revealed a pattern consistent with the cognitive reserve hypothesis. Specifically, having access to more cognitive resources in childhood was associated with compression of morbidity—longer life expectancy free of impairment and less time spent with cognitive impairment. Cross-country differences in this effect will be discussed. Overall, these findings underscore the importance of childhood cognitive stimulation for cognitive health in later life and emphasize the need for a lifespan-focused approach to studying cognitive reserve.